Research on the coordination of a marine green fuel supply chain considering a cost-sharing contract and a revenue-sharing contract - Xu, Chang-yan; Wang, Yi-qun; Yao, Di-lin; Qiu, Si-yuan; Li, Hui (Frontiers in Marine Science, 2025)
The marine green fuel supply chain is a crucial component in the development of green ports. Focusing on the issue of cooperative contracts between the port and green marine fuel supplier within the marine green fuel supply chain, first, a two-echelon marine green fuel supply chain optimization model consisting of a green marine fuel supplier and a port was constructed. Second, the changes in profits and decisions of a green marine fuel supplier and a port were compared under four scenarios: no contract, cost-sharing contract, revenue-sharing contract, and combined revenue-sharing + cost-sharing contract. Finally, the propositions were validated using numerical simulation methods. The research findings show that, in terms of revenue, the combined profits of a port and green marine fuel supplier under the combined revenue-sharing + cost-sharing contract exceeded those under the revenue-sharing contract alone. Regarding the sales price of marine green fuel and bunkering service quality, these factors peaked under the cost-sharing contract and were at their lowest under the revenue-sharing contract. An increase in the port’s investment proportion in marine green fuel bunkering service quality led to decreases in the bunkering volume, sales price, wholesale price, and bunkering service quality of marine green fuel under both the cost-sharing contract and the revenue-sharing + cost-sharing contract. Additionally, the higher proportion of revenue shared by the port with the green marine fuel supplier resulted in lower sales price, wholesale price, and bunkering service quality of green marine fuel under both the revenue-sharing contract and revenue-sharing + cost-sharing contract.